Analisis Pendekatan Gestalt Dalam Konseling Kelompok : Kajian Literatur Sistematis - Chandra, Mutiara Putri; N, Netrawati; Karneli, Yeni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Gestalt, meaning “whole,” emphasizes the importance of direct experience and the wholeness of the individual. Counselors use techniques such as empty chair dialogue, role-playing, and awareness exercises to encourage clients to integrate aspects of themselves that may be fragmented or suppressed. This approach is very useful in dealing with emotional problems, intrapersonal conflicts, and inconsistencies between students’ thoughts and behaviors. The application of the Gestalt approach in group counseling services can support the development of social skills, emotional management, and more responsible decision-making. This article was compiled using a literature review method. Previous scientific works related to the literature review are the main sources of this research. Data collection methods include books, journal articles, internet articles, and other writings related to the subject. The results of the study show that the Gestalt approach in group counseling, it can be concluded that Gestalt therapy is an approach that emphasizes self-awareness, personal responsibility, and direct experience in the present (here and now). This approach is rooted in humanistic and existential psychology, which aims to help individuals become whole, independent, and able to overcome intrapersonal and interpersonal conflicts through the process of self-integration. In group counseling, the Gestalt approach has been shown to be effective in building strong therapeutic relationships, encouraging openness among members, and creating a safe space for exploration and growth.